O espectro médio de longo termo na pesquisa e na clínica fonoaudiológica. - Master, Suely; De Biase, Noemi; Pedrosa, Vanessa; Chiari, Brasília Maria (FapUNIFESP (SciELO), 2006)
BACKGROUND: One of the great difficulties in evaluating a voice is the judgment of quality through the perceptual auditive analysis--although frequently used--, as it is influenced by socioeconomic and cultural aspects as well as individual preferences. Many are the adjectives and methods used in this assessment, especially because of the subjectivity involved in the process, leading to incompatibilities between listeners and difficulties in reaching a consensus on the use of this or that terminology. In such a context, the voice laboratory and more specifically the acoustic computerized analysis, has guided and complemented speech-language treatments. Among the several possibilities of spectrographic analysis, the (Long-Term Average Spectrum--LTAS) quantifies the quality of voices, pointing differences between gender, age, professional--spoken and sang--and dysphonic voices. The LTAS has been used a lot in researches that investigate voice. As it evidences the contribution of the glottic source and of resonance to the quality of voice, it provides objective parameters for the evaluation of this aspect which usually depends on our auditive perception. AIM: to demonstrate how LTAS can be applied in voice research and in the speech-language therapy practice, describing both the technical aspects required for the production and interpretation of results, and its limitations. CONCLUSION: The area of voice research has developed a lot in these last two decades especially because of the advent of the voice and speech laboratory. For this reason, the knowledge about the applicability of more tools for voice analysis, as the LTAS, as well as the existing need for more studies in this area, will most certainly contribute for the creation of new research areas not only in the field of professional voice but also in the field of therapy.
The long-term average spectrum in research and in the clinical practice of speech therapists
Keywords: human; larynx disorder; physiology; review; speech; speech disorder; speech rehabilitation; vocal cord; voice; Humans; Speech Acoustics; Speech-Language Pathology; Vocal Cords; Voice Disorders; Voice Quality; Voice Training; Acoustic Phonetics (00150); Sound Spectrographs (80500); Speech Perception (82700); Speech Therapy (83200); Voice Quality (95200)